Permainan Tradisi Bakuit Masyarakat Dusun Tatana : Dokumentasi Teknik Bermain - Mohd Akmal bin Mat Salleh; Humin Jusilin; Baharuddin Mohd Arus (2018)
Traditional games are a legacy handed down from generations to generations. The essence of traditional games contain values and meanings that are beneficial to the individual, society and nature. Every traditional game has its own medium, regulations and categories. The focus of this study is to visually document the information related to the ‘bakuit’, a traditional game of the ethnic Dusun Tatana who live in the district of Kuala Penyu, Sabah. The main objective of this study is to identify the techniques to play the game. The study concludes that the ‘bakuit’ has its own uniqueness pertaining to the culture and identity of the people. As such, this legacy must be preserved so that people especially the younger generation of the Dusun Tatana’s will remember and know the existence of the traditional game called ‘bakuit’.